Gender ideology of Singaporean men and women in the private sphere. - Koh, Choon Min. (2010)
This paper presents findings from a study which explored the current gender ideology within the private sphere amongst Singaporean men and women, through providing a comprehensive and detailed account of the attitude, preferences and opinions of Singaporean men and women with regards to three concepts; the “breadwinner status” within a household, men and women assuming equal rights and responsibilities and trends of gender role reversal in recent years. The later part of the paper attempts to apply Anthony Gidden’s Structuration Theory to explain and analyze the current gender role attitude of men and women with regards to the significance of social structure which provides the institutional norms, traditional norms, conventions and moral codes that functions as both constraining and enabling determinants to the gender role attitudes and behaviour Singaporean men and women.